Formulation and Evaluation of Doxylamine Succinate Fast Dissolving Buccal Films - Vidyadhara, S. (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: This study deals with the formulation of fast dissolving buccal films of doxylamine succinate is an antihistaminic commonly used for the prevention and treatment of nausea and vomiting in pregnancy. Doxylamine is a histamine H1 antagonist with pronounced sedative properties. It is used in allergies, antiemetic, and hypnotic. Doxylamine has also been administered in veterinary applications and was formerly used in Parkinsonism. The concept of fast-dissolving drug delivery emerged from the desire to provide the patient with a more conventional means of taking their medication. Materials and Methods: In the present research work, various trials were carried out using film forming agents such as maltodextrin, gum karaya, and xanthan gum to prepare an ideal film. Emulsion evaporation method was used for the preparation of films. Results and Discussion: The prepared films were evaluated for weight uniformity, drug content, film thickness, folding endurance, dispersion test, and curling. The in vitro dissolution studies were carried out using simulated salivary fluid (pH 6.8 phosphate buffers). About 98% of the drug was found to be released from the film prepared with the drug excipient interaction studies carried out by differential scanning calorimetry analysis and Fourier transform infrared studies, and the results revealed that there were no major interactions between the drugs and excipients used for the preparation of films.